Efektifitas Simulasi Resusitasi Jantung Paru Terhadap Kemampuan Penatalaksanaan Resusitasi Jantung Paru Anggota Brimob - Prima Dewi Kusumawati; Adetya Wahyu Dwi Jaya (UIMA Press, 2019)
Introduction: Lack of community's ability to do first aid to victims who experience cardiac arrest is due to the short of knowledge that is owned by the community, especially about how to perform lung heart resuscitation so that the death rate due to cardiac arrest increases. Objective: The aim of the study was to determine the effectiveness of the simulation of pulmonary resuscitation on the ability to manage pulmonary resuscitation in Brigade Mobile Members. Method: The study design was pre-experimental with a one-group pre post test approach. Respondents were taken by accidental sampling technique. The population of all members of Brigade Mobile in Company 1 Battalion C Pioneer of Brigade Mobile Unit of Regional Police East Java as many as 100 people, a sample of 25 respondents. Result: The results showed that all Brigade Mobile Members had the ability with the category of less skilled in performing pulmonary resuscitation before simulating 25 (100%) Respondents, almost all Brigade Mobile members had the ability with skilled categories in performing cardiac pulmonary resuscitation after simulation, which was 22 (88.0%). The results of data analysis showed that the significance level of p-value = 0,000. Conclusion: there was an effect on the simulation of Pulmonary Resuscitation on the ability to manage Pulmonary Resuscitation (RJP) of Brigade Mobile Members in Company 1 Battalion C Pioneer of Brigade Mobile Unit of East Java Regional Police. The more often simulations are carried out, the more skilled is the ability of Brigade Mobile members to carry out basic life support, because by providing simulations Brigade Mobile members not only can hear but also see firsthand the actions that can be taken when finding victims with cardiac arrest.